2007
DOI: 10.1038/sj.pcan.4501007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses of benign and malignant prostate epithelial cells in formalin-fixed paraffin-embedded whole-mounted radical prostatectomy specimens

Abstract: Formalin-fixed paraffin-embedded (FFPE) prostate specimens are rich sources of molecular pathological information. However, FFPE-based microarray analysis of tissue samples may be hampered by the degradation and chemical alteration of RNA molecules due to the preservation procedure. In this report, we employed a probe analyses of Affymetrix oligonucleotide arrays at individual probe level to compensate for the potential loss of gene identifications associated with compromised mRNA quality in FFPE preparations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…KLK2 and PSA are androgen regulated serine proteases expressed in prostate epithelial cells and upregulated in prostate cancer [63]. Two ets related transcription factors observed in this study, ets-related gene ( ERG ) and Sam pointed domain ets transcription factor (SPEDF ) [16] are known to be upregulated in prostate tumor epithelial cells [64,17,18]. The importance of the ERG gene is supported by its frequent involvement in complex rearrangements with a host of other gene fusion partners.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…KLK2 and PSA are androgen regulated serine proteases expressed in prostate epithelial cells and upregulated in prostate cancer [63]. Two ets related transcription factors observed in this study, ets-related gene ( ERG ) and Sam pointed domain ets transcription factor (SPEDF ) [16] are known to be upregulated in prostate tumor epithelial cells [64,17,18]. The importance of the ERG gene is supported by its frequent involvement in complex rearrangements with a host of other gene fusion partners.…”
Section: Discussionmentioning
confidence: 98%
“…normal epithelia, we and others observed genes elevated in prostate cancer epithelial cells including kallikrein proteins 2 (KLK2) , and 3 (KLK3 , or PSA) [16]. KLK2 and PSA are androgen regulated serine proteases expressed in prostate epithelial cells and upregulated in prostate cancer [63].…”
Section: Discussionmentioning
confidence: 99%
“…LCM is a well-established technique in prostate tissue [7,15,16]. However, to our knowledge, it has not been described in FFPE diagnostic needle biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Laser-capture microdissection (LCM) allows enriched cell populations to be accurately isolated from heterogeneous tissue, hence facilitating analysis of different components from a single tissue sample [6,7]. Real-time PCR (QPCR) uses small amplicon sizes which are more suited to the short templates derived from degraded RNA as compared with standard PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that similar techniques have been successfully performed on breast, gastric, colonic, and prostatic epithelium suggesting that this methodology is a powerful means for screening of new biomarkers (23,52-54). As pathologists our primary goal was to identify candidates for the generation of immunohistochemical reagents as immunohistochemistry is available in all pathology departments and all pathologists are quite comfortable with the technique.…”
Section: Discussionmentioning
confidence: 99%